Predicting functional performance and locomotion of children with cerebral palsy - Lewandowska, Renata; Krajewski, Stanisław; Juraszek, Karolina (Journal of Education, Health and Sport, 2018)
The aim of this study was to present the factors affecting prediction of the functioning and locomotion of children with cerebral palsy.Cerebral palsy is one of the most common causes of disability among children. When predicting the future of a child, its functioning mode and locomotion, many factors should be considered, i.e. the degree of brain injury, the moment of implementing therapy, cognitive abilities of the child, level of mental retardation, epileptic seizures, hearing and vision impairment, etc. The goal of the therapy and its effectiveness depends on the appropriate assessment, and this determines the prediction of the patient’s future. The Gross Motor Function Classification System (GMFCS) can be a useful tool in predicting a child’s functional performance.